A influência da consciência coletiva na concretização das normas internacionais do direito do trabalho - David, Ana Paula Sawaya Pereira do Vale Bernardes (2018)
This thesis analyzes the formation of a "collective conscience" that favors the protection of labor rights not only in the internal sphere of each country, but in an international scope. In this way, by deepening the mechanisms of action of the International Organizations, especially the ILO, it will be avoided that strictly economic interests overlap with the interests of the vast majority of the world population that needs human rights implementations. second generation, namely, social rights. The strengthening of this conscious collective conscience necessarily involves the strengthening of international organizations, the revision of the perception of national states about their limitations and the extent of sovereignty. It also stresses the importance of a more direct dialogue between international bodies and social actors that have gained relevance during the twentieth century, namely individuals and large business and economic conclomerates